NGF monoclonal antibody DS002 alleviates chemotherapy-induced peripheral neuropathy in rats - Liang, Zhi-juan; Tan, Jie; Tang, Lei; Xie, Zuo-bin; Chen, Gan-jun; Liu, Guo-jian; Yuan, Lin; Wang, Kai-xin; Ding, Hua-ping; Qiu, Hong; Wang, Qi; Wang, Gui-feng; et al. (Acta pharmacologica Sinica, 2022)
Chemotherapy-induced peripheral neuropathy (CIPN) is one of the pervasive side effects of chemotherapy, leading to poor quality of life in cancer patients. Discovery of powerful analgesics for CIPN is an urgent and substantial clinical need. Nerve growth factor (NGF), a classic neurotrophic factor, has been identified as a potential therapeutic target for pain. In this study, we generated a humanized NGF monoclonal antibody (DS002) that most effectively blocked the interaction between NGF and tropomyosin receptor kinase A (TrkA). We showed that DS002 blocked NGF binding to TrkA in a dose-dependent manner with an IC 50 value of 6.6 nM; DS002 dose-dependently inhibited the proliferation of TF-1 cells by blocking the TrkA-mediated downstream signaling pathway. Furthermore, DS002 did not display noticeable species differences in its binding and blocking abilities. In three chemotherapy-induced rat models of CIPN, subcutaneous injection of DS002 produced a significant prophylactic effect against paclitaxel-, cisplatin- and vincristine-induced peripheral neuropathy. In conclusion, we demonstrate for the first time that an NGF inhibitor effectively alleviates pain in animal models of CIPN. DS002 has the potential to treat CIPN pain in the clinic.